Failure analysis of woven Kevlar/Epoxy under uniaxial tension - Rahimi, Norzihan; Hussain, Ahmad Kamil; Shaik Dawood, Mohd. Sultan Ibrahim; Mohd Alias, Adib Zulfadhli; Md Yusoff, Muhamed Hafiy Afiq; Mahmud, Jamaluddin (Science Publishing Corporation Inc, 2018)
The increasing demand for newer materials with versatile properties such as high strength-to-weight ratio; has made fiber reinforced composite materials a favourable choice in various applications, particularly in the automotive, aerospace, marine, sports and defense industries. Moreover, the properties of a composite material could be tailored for specific functions or applications. Despite its many attractive features, composite material fails in a complex manner involving matrix failure, fiber failure and delamination. This failure behaviour needs to be well established. The objective of this study is to perform failure analysis on a woven Kevlar/Epoxy composite laminate subjected to uniaxial tension and establish its failure trend. The lamination sequence is (θ4/θ4/-θ4)S where the angle, θ, ranges from 0° to 90°. The failure analysis was carried out using a commercial finite element software, Ansys and comparisons were made using analytical methods (Matlab). The values of stresses were computed and Maximum Stress Theory was employed to check for failure. The trend of failure, in terms of the failure curves (normalized first ply failure and last ply failure loads), for woven Kevlar/Epoxy was established. This study had produced new failure datas for woven Kevlar/Epoxy and thus, contributes significant knowledge about the failure behaviour of composite materials.